Conspicuously Concealed: Federal Funding, Knowledge Production, and the Criminalization of Gun Research. (February 2022) - Carlson, Jennifer; James, Rina
A popular narrative in the U.S. gun debate concerns federal funding of gun research: Because of a right-wing backlash against gun-related public health research (centered on the controversial Kellermann et al. study), federal funding of gun research has been frozen since the mid-1990s. How accurate is this popular "funding freeze" narrative—or is the federal funding of gun research better described as a "chill"? If the latter, what kinds of funding have persisted within this "chill"? Drawing on public data on funded project abstracts from 1996 to 2016 from three major federal institutes (the National Institute of Justice, the National Science Foundation, and the National Institutes of Health), this paper shows that despite funding cuts to the Centers for Disease Control and Prevention (CDC), federal funding for gun research has continued, especially for studies that construct the focus of their study as gun crime . Specifically, we find that a criminal justice approach to the study of guns and gun-related topics dominates the project abstracts analyzed and that this approach also casts a shadow on other approaches—especially public health and social justice approaches—to the research of guns. Examining federally funded gun research from a social constructionist lens provides insight not just into federal funding of gun research but also into the dominant framings of gun policy within the United States: criminal justice approaches to gun research may reinforce an understanding of gun violence as a problem of crime and justify criminalizing strategies in gun policy.